Jacob Van Etten on Vulnerability, climate change adaptation and local food systems - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Vulnerability, climate change adaptation and local food systems Presentation by Jacob Van Etten from Bioversity International at the seminar on Closing the gender gap in farming under climate change held 19 March 2015 in Paris. Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action